If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a + -4 = 6a + 12 Reorder the terms: -4 + 5a = 6a + 12 Reorder the terms: -4 + 5a = 12 + 6a Solving -4 + 5a = 12 + 6a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6a' to each side of the equation. -4 + 5a + -6a = 12 + 6a + -6a Combine like terms: 5a + -6a = -1a -4 + -1a = 12 + 6a + -6a Combine like terms: 6a + -6a = 0 -4 + -1a = 12 + 0 -4 + -1a = 12 Add '4' to each side of the equation. -4 + 4 + -1a = 12 + 4 Combine like terms: -4 + 4 = 0 0 + -1a = 12 + 4 -1a = 12 + 4 Combine like terms: 12 + 4 = 16 -1a = 16 Divide each side by '-1'. a = -16 Simplifying a = -16
| 9x(x+9)=0 | | x^2+15x-21=0 | | 6(3y-2(y-1))-2+7y=0 | | 1x=32x-3 | | 5(5-3x)=12-4(x-3) | | x^2=-48 | | 4y^2-6=5y | | 2lnx+ln(2x-1)=ln(5x+2) | | 5x+20=2x-10(x+10) | | 5x+20=2x-10 | | (4x-3)(3x+5)= | | 5x+20=65 | | 3m+2n+2= | | 8p^2=-56p | | 4*6*x+(6x*5x)= | | 3[y+4]=-9 | | 7(3t-2)=28 | | 4(2y+3)=52 | | 5(y-2)=60 | | 5k-2=33 | | 3(x+6)=6(2+y) | | 3x+8=-4x-6 | | 4(n+9)-3(2+n)= | | 5(6+n)-2(n-2)= | | 6r+2(r+4)= | | 2+3xy-4xy+6= | | (2x+6)(5x-13)=0 | | x-1.6x-2.6=0.6x+2.2 | | 2(2-x)-4(2x-1)=4(x-1)-3(2x-3) | | 0.33333+x=-0.53333 | | 4.8x+2=3.8x | | 4.8-2=3.8x |